Physical load imposed on soccer players during small-sided training games - Mallo, J.; Navarro, E. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: The aim of this study was to examine the kinematical, physiological and technical load imposed on soccer players during three typical small-sided 3-a-side training games carried out in an artificial grass 33x20 m surface. Methods: Kinematic analysis was carried out with a bidimensional photogrammetric video system. Heart rate was recorded at 5 s intervals using Polar Accurex Plus heart rate monitors and expressed in relation to individual maximal heart rate (HRmax). Technical parameters were registered using a specifically designed notation sheet. Results: The overall intensity of these three small-sided games was superior than the experienced during competitive matches. Distance covered (747-749 vs 638 m) and mean heart rate (173 vs 166 b·min-1) were higher (P<0.05) in the drills without goalkeepers. The inclusion of goalkeepers reduced the tempo of the game as players performed less (P<0.05) high-intensity running and increased (P<0.05) low-intensity activities. Time spent exercising at intensities between 76-85% HRmax was lower (P<0.05) in the game without goals, whereas the presence of goalkeepers reduced (P<0.05) activities performed exceeding 86% HRmax. Conclusion: The results of this study suggest that small-sided games can be used effectively to develop the specific endurance capacity of football players. The integration of these drills by coaches during the regular training schedule can help replicating the demands experienced during real match-play.